Evaluación de sistemas biológicos y químicos para tratamientos de aguas residuales en la ciudad de Bahía de Caráquez - Dueñas Oyaneder, Darwin Alejandro (2023)
Currently, contamination of tributaries in oxidation lagoons is one of the main environmental problems. Therefore, the application of treatment systems that provide a solution to this problem is required. The objective of this research was to evaluate the biological and chemical systems for the treatment of wastewater tributaries from Bahía de Caráquez city, Manabí, Ecuador. For the development of the work, a 22 factorial design was applied, with 4 treatments and 4 repetitions. Commercial aluminum sulfate coagulants and flocculants were used applying the jar test. The wastewater and the treated water were characterized taking into account parameters such as pH, color, EC, TDS, ST and turbidity. These values were verified with table 10 of annex 1 of Book VI of the TULSMA. The results obtained demonstrate that the application of chemical and biological substances are favorable in treatments with and without lime. Good removal efficiencies were verified in the parameters evaluated: turbidity, T7 being the best treatment with 97.3% removal; pH obtained values of 5 and 7 in T8 and T9; SDT reached 1320 mg/l in T2 and the color presented 150 color units in T2. It was determined that the pH of the wastewater is within the permissible limits of the TULSMA. Finally, a proposal for a mitigation plan was prepared for the socio-environmental impacts identified in the oxidation lagoon.